Real estate Issue in French real estate legislation in Algeria during the militaryperiod (1830-1870( - Boubaker, sammari (The Algerian Historical Journal, 2026)
The most important French real estate legislation in Algeria during themilitary period rule (1830 - 1870) from the Clauzelin8 September 1830 AD, which included the confiscation of the Beylik lands, and the Decree of4 June 1843, which included the confiscation of Habous lands, and the Amritas of 1October 1844 and July 1846, which established the foundations of the occupation, then the Real Estate Charter on16 Jun, 1852, and the most important of all is the Senatus-Consulta LawThese laws constituted a major tool in the service of colonialism and enabled settlement and resettlement by dispossessing Algerians of their property and granting it to colonists, which led to changing the nature of the collective ownership system established by tribal customs to individual ownership, which had serious repercussions on Algerian society such as poverty and marginalization